A survey of the writing instructional practices of Nebraska teachers of students with visual impairments. Issue 4 (8th August 2021) - Hebert, Michael; Savaiano, Mackenzie E.
ABSTRACT: This paper describes a survey of teachers of students with visual impairments (TVIs) in Nebraska. Questions addressed their preparation to teach writing, writing practices, and beliefs about writing instruction. Twenty-four of 60 TVIs in Nebraska responded to the survey, and 19 answered all questions. Teachers were split on their preparation to teach writing (50% indicated receiving adequate training), but slightly to moderately agreed that they knew how to use writing to support their students' needs. The TVIs unanimously agreed that all writing purposes (e.g., for fun, to demonstrate knowledge, for daily living activities) are appropriate for students who are functionally blind, students who have low vision, and students with multiple disabilities or deaf-blindness. However, they were split on whether writing instruction was their responsibility (47.8% agreed, 52.2% disagreed) and varied in the use of writing practices across different groups of students (e.g., 74% of TVIs felt writing to inform was appropriate for students who are functionally blind, whereas only 42% and 11% felt this was appropriate for students with low vision and multiple-disabilities, respectively). The implications of this study are limited due to the small number of participants, but the results represent 40% of the total number of Nebraska TVIs.